The Polemical Cosmogony in the Doxologies of Amos (4:13; 5:8; 9:5–6) - Ayali-Darshan, Nogah (2025)
The paper explores the doxologies in the book of Amos, arguing that they articulate a polemical viewpoint distinct from prevailing biblical and ancient Near Eastern notions about the formation of the sea, mountains, wind, and God’s abode. Central to the comprehension of this cosmogony is the recurring phrase in Amos 5:8d and 6:9c, “(He) who summons the waters of the sea and pours them on the surface of the earth.” While previous scholars have understood this phrase as referring to the primeval Flood, a tsunami event, or Levantine torrential rain, the present paper suggests a cosmogonic interpretation, in line with its context. Subsequent elements in the same series of texts are interlinked with this portrayal, emphasizing the unified—and polemical—perspective of the doxologies. This new explanation also has ramifications for the dating and composition of the doxologies in the book of Amos.
Keywords: polemical approach; Cosmogony; Amos; doxologies